Does Successful Innovation Require Large Urban Areas? Germany as a Counterexample. (27th May 2021) - Fritsch, Michael; Wyrwich, Michael
Abstract: Popular theories claim that innovation activities should be located in large cities because of more favorable environmental conditions that are absent in smaller cities or peripheral areas. Germany provides a counterexample to such theories. We argue that a major reason behind the geography of innovation in Germany is the country's pronounced legacy of political fragmentation that created a decentralized settlement structure, shaped the geographic distribution of universities and public research institutions, and brought about a rather uniform and local access to finance. We show how political fragmentation influenced the emergence of historic centers of knowledge production and impacts the positioning of innovation activities today. We conclude that institutional factors should play a more prominent role in theories that aim at explaining the spatial distribution of innovation activities.